Serum Levels of Fibroblast Growth Factor 19 Correlate with the Severity of Diarrhea and Independently from Intestinal Inflammation in Patients with Inflammatory Bowel Disease or Microscopic Colitis - Ivan Lyutakov; Radislav Nakov; Hristo Valkov; Rositsa Vatcheva-Dobrevska; Borislav Vladimirov; Plamen Penchev (Turkish Journal of Gastroenterology, 2021)
Background: In chronic diarrhea patients, massive over-reporting symptom-based criteria for functional bowel disorders are pitfalls. There is currently no objective biomarker that may provide a correct correlation with the severity of chronic diarrhea. To clarify the role of fibroblast growth factor-19 (FGF-19) as a biomarker of objective measurements of the severity of diarrhea in comparison with a patientreported outcome, based on the Bristol Stool Form (BSF) Scale. Methods: Consecutive 100 patients with chronic diarrhea underwent standard investigations with laboratory tests, fecal calprotectin (FC), endoscopy with biopsies, and serum FGF-19. All patients and 14 healthy controls completed a diary recording, BSF, and stool frequency. Results: We found that irritable bowel syndrome with diarrhea (IBS-D) n = 21/23 (91%) reported a high number on BSF ≥6, compared to patients with inflammatory bowel diseases (IBD) 56/77 (72%) with BSF ≥ 6 (P = .011). FGF-19 median serum levels were significantly lower in Microscopic colitis (0.010 pg/mL) and IBD patients (0.009 pg/mL) compare to IBS-D (266.9 pg/mL) and high levels in healthy subjects (463 pg/mL) (P < .001). Strong inverse correlation of FGF-19 with the stool frequency/day and stool index was found (r = −0.800, P < .001; r = −0.739, P < .001), independently from disease activity (r = −0.718, P = .001; r = −0.792, P = .001). Conclusion: Serum FGF-19 can become a new biomarker for evaluating the severity of diarrhea with objectively and independently from intestinal inflammation. FC and FGF-19 are predictive biomarkers for the organic cause of diarrhea. Cite this article as: Lyutakov I, Nakov R, Valkov H, Vatcheva-Dobrevska R, Vladimirov B, Penchev P. Serum levels of fibroblast growth factor 19 correlate with the severity of diarrhea and independently from intestinal inflammation in patients with inflammatory bowel disease or microscopic colitis. Turk J Gastroenterol. 2021; 32(4): 374-381.